Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $|z|=1$, show that: $$\mathrm{Re}\left(\frac{1 - z}{1 + z}\right) = 0$$

I reasoned that for $z = x + iy$, $\sqrt{x^2 + y^2} = 1\implies x^2 + y ^2 = 1$ and figured the real part would be:

$$\frac{1 - x}{1 + x}$$

I tried a number of manipulations of the equation but couldn't seem to arrive at any point where I could link the two to show that the real part was = 0.

share|cite|improve this question
write $z=re^{i\theta}$ and observe that $r=1$ and $e^{i\theta} = cos \theta + i sin \theta$. Now manipulate the given condition. – Dilawar Mar 11 '12 at 12:39
You can not calculate the real part like that (see anon's answer/comment below). – AD. Mar 15 '12 at 7:58
up vote 17 down vote accepted

The easy method to do this kind of exercise is to notice that $Re(z)=0$ if and only if $z=-\overline z$. Notice that if $|z|=1$ then $\overline z=\frac{1}{z}$.

In your case $$ \overline{\left(\frac{1-z}{1+z}\right)}=\frac{1-\overline z}{1+\overline z}=\frac{1-\frac{1}{z}}{1+\frac{1}{z}}=\frac{z-1}{1+z}=-\frac{1-z}{1+z}$$

Usually, the replacement of the algebraic form $z=x+iy$ makes things much more complicated in problems like this. First you should try applying the standard results from the general case, such as $|z|^2=z\overline z$, or $z \in \Bbb{R}$ if and only if $z=\overline z$, etc.

share|cite|improve this answer

Let $z=a+bi$, where $a^2+b^2=1$ and $z\neq -1$. Then $$\begin{eqnarray} \Re\left(\frac{1-z}{1+z}\right) &=&\Re\left(\frac{(1-z)\overline{(1+z)}}{|1+z|^2}\right)\\ &=&\Re\left(\frac{(1-a-bi)(1+a-bi)}{(a+1)^2+b^2}\right)\\ &=&\Re\left(\frac{1-(a^2+b^2)-2bi}{(a+1)^2+b^2}\right)\\ &=&\Re\left(\frac{-2bi}{(a+1)^2+b^2}\right)=0\end{eqnarray}$$

share|cite|improve this answer

Using polar form of a complex number, $z=e^{i\theta},\quad\theta\in\mathbb{R}$.

Hence $\frac{1-z}{1+z}=\dfrac{1-e^{i\theta}}{1+e^{i\theta}}=\dfrac{e^{-\frac{i\theta}{2}}-e^{\frac{i\theta}{2}}}{e^{-\frac{i\theta}{2}}+e^{\frac{i\theta}{2}}}=\dfrac{-2i\sin\frac{\theta}{2}}{2\cos\frac{\theta}{2}}=-i\tan\frac{\theta}{2}$

share|cite|improve this answer
How did you get from term 2 to 3 and from term 3 to 4? – stariz77 Mar 18 '12 at 22:36
@stariz77 Multiplying numerator and denominator by $e^{-\frac{i\theta}{2}}$ and then using the formula $e^{ix}=\cos x+i\sin x$. – Tapu Mar 19 '12 at 8:02

Since we are adding multiple proofs, here are two more.

1) Geometric proof.

enter image description here

$\displaystyle z$ corresponds to point $\displaystyle B$. $\displaystyle 1+z$ corresponds to $\displaystyle H$ and $\displaystyle 1-z$ to $\displaystyle G$.

$\displaystyle ACGD$ and $\displaystyle ADHB$ are rhombii, with $CD$ parallel to $\displaystyle AH$. In rhombii the diagonals intersect at right angles, and so $\displaystyle AG$ is perpendicular to $\displaystyle AH$.

Thus $\displaystyle \frac{1-z}{1+z} = ci$ for some $\displaystyle c$.

2) Using vectors.

We refer to the above figure.

$\displaystyle H = (1+\cos \theta, \sin \theta)$.

$\displaystyle G = (1- \cos \theta, -\sin \theta)$.

Their dot product = $\displaystyle (1 + \cos \theta)(1- \cos \theta) - \sin^2 \theta = 1 - \cos^2 \theta - \sin^2 \theta = 0$

So $\displaystyle \vec{AH}$ and $\displaystyle \vec{AG}$ are perpendicular.

Incidentally, the converse is also true:

If $\displaystyle \text{Re}\left(\frac{1-z}{1+z}\right) = 0$, then $\displaystyle |z| = 1$.

share|cite|improve this answer

Hint $\: $ Realizing the denominator produces a purely imaginary numerator, i.e.

$$\displaystyle\ z\bar z\: =\: 1\ \:\Rightarrow\:\ \frac{(1-z)\:(1+\bar z)}{(1+z)\:(1+\bar z)}\: =\: \frac{\bar z-z}{|1+z|^2}\: =\: \frac{r\:i}{s},\ \ r,s\in \mathbb R$$

Note $\ $ This is an instance of the powerful method of rationalizing denominators to simplify arithmetic of algebraic numbers or functions. Generally, $\rm F$-rationalize means coerce to an element of the base ring $\rm F$ of an algebraic extension, which classically is $\mathbb Q = $ rationals. Above we have the base ring $\rm F =\mathbb R\subset \mathbb R[{\it i}] = \mathbb C,\:$ so rationalize means realize.

share|cite|improve this answer

I want to point out that the problem in your approach is that, generally,

$$\mathrm{Re}\left(\frac{1-z}{1+z}\right) \ne \frac{1-\mathrm{Re}(z)}{1+\mathrm{Re}(z)}.$$

In other words, just because there's a Re on the left of the equation doesn't mean you can replace a complex variable $z$ with its real part $x$; that's tantamount to switching the order of evaluation of two functions composed (as in $f\circ g$ vs. $g\circ f$, here with $f=\mathrm{Re}$ and $g(z)=\frac{1-z}{1+z}$).

The general approach you want to take is replacing $z$ with $x+yi$, then trying to get the whole thing inside the real part in the form $\text{blah}_1+\text{blah}_2i$, where both $\text{blah}$s are entirely real, so you can just chop off $\text{blah}_2$ to finish evaluating. Frequently this process involves slapping the conjugate $x-yi$ in there somewhere to make things real.

share|cite|improve this answer
Not feeling foo and bar today? – Alex Becker Mar 11 '12 at 15:05

Yet another approach, is to note that $Re(\overline z_1z_2)=z_1 \cdot z_2$, where $\cdot$ denotes the euclidean dot product in $R^2$.

Let $z=x+iy$ for $x,y$ in $R$, then we have $Re(\frac{1-z}{1+z})=\overline{1-z}{\frac{1}{1+z}}=(1-x,y)\cdot (\frac{1+x}{1+2x+x^2+y^2},\frac{-y}{1+2x+x^2+y^2})=\frac{1-(x^2+y^2)}{2+2x}=0$

share|cite|improve this answer
Re$(\bar i\bar i)=-1$ but $i\cdot i=1$ if I read you correctly. And $\overline{\frac1{1+z}}$ is proportional to $(1+x,y)$, not $(1+x,-y)$. – Did Mar 15 '12 at 9:04
oh, you are right. I think it is fixed now. Thanks! – Henrik Mar 15 '12 at 9:33
  1. The map $$T:z\mapsto \frac{1-z}{1+z}$$ is a Möbius transform.
  2. It is well known that Möbius transforms maps circles into straight lines or circles.
  3. By 1 and 2 it is sufficient to check the image of three points in order to decide the image of $\{z:\,|z|=1\}$.

Now, $$T(1)= 0$$ $$T(-1)= \infty$$ $$T(i)=\frac{1-i}{1+i}= \frac{(1-i)\overline{(1+i)}}{|1+i|^2}=\frac{(1-i)^2}{2} = \frac{-2i}{2}=-i$$ That is the image of the unit circle is the imaginary axis and in particular $$\Re\frac{1-z}{1+z}=0, \qquad \text{when $|z|=1$}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.